MANAGEMENT OF THE ASWAJA AN-NAHDLIYYAH-BASED LOCAL CURRICULUM IN STRENGTHENING STUDENTS' CHARACTER - Sukarman Sukarman; Muthofi’ah Muthofi’ah; Subaidi Subaidi; Mahalli Mahalli; Rahimah Embong; Abdulasi Kalupae (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
One of the serious problems in education is the imbalance between knowledge and character among students. Ideal education is to balance knowledge and character. The formation of students' character is very necessary to form a generation with noble character, one of which is by integrating Local based curriculum Aswaja An-Nahdliyyah into the curriculum. This curriculum teaches the importance of religious attitudes, politeness, respect for parents, tolerance, and maintaining manners and ethics in society. This study aims to describe the management of Aswaja An-Nahdliyyah based lokal curriculum in strengthening the character of students at Madrasah Aliyah Miftahussalam Wonosalam Demak. This study will answer how the management and the strategy of the Local based curriculum strengthen student’s character, and what the supporting and inhibiting factors are for the implementation of the management of local-based curriculum in strengthening the student’s character. This study is a qualitative descriptive study. Data collection uses interview, observation, and documentation techniques. The data will be analyzed using data reduction, data presentation, and finally drawing conclusions. The results of this study include 1) Local based curriculum management consists of the planning, organizing, implementing, and evaluating processes. 2) strategies for strengthening character through classroom learning, and through the habituation of daily attitudes and behaviors 3) Supporting factors for the implementation of the curriculum are that the madrasah is in an Islamic boarding school environment and students have the same ideology, namely Nahdlatul Ulama. Students' social interactions outside of school and their lack of communication with parents act as inhibiting factors.